Determination of methoxypolybrominated diphenyl ethers in the coastal marine environment using solid-phase extraction and gas chromatography coupled with negative chemical ionization mass spectrometry - Gao, Wen; Sun, Xiumei; Jin, Yanjian; Hao, Qing; Fu, Yu; Ye, Maosheng; Yang, Chenghu; Guo, Yuanming (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2022)
Methoxypolybrominated diphenyl ethers （Me O-PBDEs） were widely present in marine organisms and the marine environment.An analytical method of six methoxypolybrominated diphenyl ethers for biological samples and sediment samples from Xiangshan Sea area using solid-phase extraction and gas chromatography coupled with negative chemical ionization mass spectrometry was developed and optimized.The developed method exhibited satisfying linearity in the range of 0.1-20.0μg·L-1 （R2>0.999）.The detection limit （LOD） and limit of quantitation （LOQ） for Me O-PBDEs were 0.13-0.22μg·kg-1and 0.42-0.72μg·kg-1respectively.The spiked recovery was 71.2%-116.2%.The method was applied to the analysis of marine organisms and sediments collected from Xiangshan sea area.All kinds of Me O-PBDEs were not detected in sediment samples.Only 6-Me O-BDE-47 was detected in algae samples with low concentration.Three Me O-PBDEs were detected in other biological samples,and the ratio of detection was31.3%with a concentration range of 0.21-2.72